Molecular Profiling of Decompensated Cirrhosis by a Novel MicroRNA Signature - Garcia Garcia de Paredes, Ana (Hepatol Commun, 2020)
Noninvasive staging of decompensated cirrhosis is an unmet clinical need. The aims of this study were to characterize and validate a novel microRNA (miRNA) signature to stage decompensated cirrhosis and predict the portal pressure and systolic cardiac response to nonselective beta‐blockers (NSBBs). Serum samples from patients with decompensated cirrhosis (n = 36) and healthy controls (n = 36) were tested for a novel signature of five miRNAs (miR‐452‐5p, miR‐429, miR‐885‐5p, miR‐181b‐5p, and miR‐122‐5p) identified in the secretome of primary human hepatocytes and for three miRNAs (miR‐192‐5p, miR‐34a‐5p, and miR‐29a‐5p) previously discovered as biomarkers of chronic liver disease. All patients had ascites, which was refractory in 18 (50%), and were placed on NSBBs for variceal bleeding prophylaxis. In all patients, serum miRNAs, hepatic venous pressure gradient, and an echocardiogram study were performed before and 1 month after NSBBs. Patients with cirrhosis had lower serum levels of miR‐429, miR‐885‐5p, miR‐181b‐5p, miR‐122‐5p, miR‐192‐5p, and miR‐29a‐5p (P < 0.05). Baseline serum miR‐452‐5p and miR‐429 levels were lower in NSBB responders (P = 0.006). miR‐181b‐5p levels were greater in refractory ascites than in diuretic‐sensitive ascites (P = 0.008) and correlated with serum creatinine. miR‐452‐5p and miR‐885‐5p were inversely correlated with baseline systemic vascular resistance (ρ = −0.46, P = 0.007; and ρ = −0.41, P = 0.01, respectively) and with diminished systolic contractility (ρ = −0.55, P = 0.02; and ρ = −0.55, P = 0.02, respectively) in patients with refractory ascites after NSBBs. Conclusion: Analysis of a miRNA signature in serum discriminates between patients with decompensated cirrhosis who show more severe systemic circulatory dysfunction and compromised systolic function after beta‐blockade and those more likely to benefit from NSBBs.